Vascular Root Biomass and N Concentrations at Two Depths in an Alberta Peatland Subjected to Increasing Nitrogen Deposition, 2014-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). From 2014-2015, we examined the effects of N addition on root production and nitrogen assimilation in those roots by measuring root biomass at two depths and root production over one and two years. Root biomass in the 0-15 cm and 15-30 cm depth increments in peat increased with increasing N input; the response was similar in the two depth increments. Root production integrated over the top 30 cm of peat increased with increasing N input at a rate of 5.3 g m -2 yr -1 with an increase in N input of 1 kg N ha -1 yr -1 . Water addition alone had no significant effect on root biomass (p > 0.72) or root production. Given the rather consistent finding increasing N deposition stimulates aboveground vascular plant biomass and production, and our results that root biomass and production at Mariana Lakes Bog are stimulated as well, further work on belowground responses seems warranted.